DEPOSITIONAL ENVINRONMENT AND PALEOCURRENT THE MIDDLE OF WARUKIN FORMATION BASED ON SEISMIC AND WELL LOG DATA IN NORTH-EAST PART BARITO BASIN, SOUTH KALIMANTAN - Yuniardi, Yuyun; Mardiana, Undang; Mohammad, Febriwan; Nur, Andi Agus; Alfadli, Muhammad Kurniawan (Bulletin of Scientific Contribution, 2020)
Explorations in the Barito basin has started nearly 100 years and was marked by the discoveryof the Tanjung Field in 1938 (Maso at all 1993). The middle of Warukin Formation is one of thereservoir formation in the Barito basin of North-Northeast. Barito Basin is located betweenSundaland in the west and Meratus in the east (Satyana, Awang.1994). An understanding of thedepositional environment and paleo-current will be very useful for the exploration and fielddevelopment optimization of oil and gas. The data used in this researcher seismic 3D data and well data. From the existing data createdseismic facies maps and correlation maps well with the markers used datum is the Top FormationMiddle Warukin. Downlap termination pattern found on the seismic line 75H - 37 at the lower limit indicates thetime of formation of this facies occur sea level rise. Configuring the parallel reflection pattern -subparallel and divergent indicate the depositional environment is shelf / platform or deltaplatform (Serra, O, 1990). Coarsening upward to fining upward pattern relatively evolved fromwireline log analysis, in which a pattern is formed on the shore face transgressive delta thenserrated pattern formed in the shelf. Based on the seismic data and log data as well as supportingdata from the regional geology of the Barito Basin, it can be interpreted that the study area isformed on the delta depositional environment - shelf. Paleo-current study area can be determined based on seismic facies maps and regionalconditions Barito Basin. Of seismic facies maps can be interpreted Paleo-current direction isrelative to the south - west with relative sediment supply from the north - east.